Model misfit - Smale, Holly (Smale, Holly. Geek girl (Series), 2015)
Harriet Manners is, to the outside world, a former geek who grew up beautiful and became a model. Secretly, Harriet remains a geek, and though she is at the top of the modeling world, she still feels out of place. When Yuka Ito invites her out to Japan to model for her new label, Harriet jumps at the chance to visit Tokyo for the summer and get away from it all--even if it means taking her crazy Grandma Bunty along, and also risking the chance of running into her ex-boyfriend.